SETTLEMENT OF PROBLEM FINANCING THROUGH THE EXECUTION OF MORTGAGE AUCTIONS AT THE STATE WEALTH AND AUCTION SERVICE OFFICE AT BANK ACEH SYARIAH SISINGAMANGARAJA BRANCH OFFICE - Aulia, Nafra; Anggraini, Tuti; Syakir, Ahmad (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
The decline in the customer's business triggers non-performing financing where the customer is not good at managing his business so that he cannot fulfill his obligations to pay existing financing, and the lack of prudence in analyzing customer data is also a negligence for the bank so that it increases the amount of non-performing financing every year. This research was conducted in order to find out what factors cause non-performing financing, and how the settlement strategy is in bank aceh syariah. This research uses a descriptive qualitative research method with a case study approach to gain an in-depth understanding of the case under study, namely the settlement of problematic financing in a mortgage auction through KPKNL. While the data source of this research uses primary data, namely those obtained during interviews and observation activities to related informants, while secondary data is in the form of documents and previous literature. The results of the study found that the factors causing problematic financing are internal factors, namely the bank itself, and external factors that exist in the customer service. And the settlement carried out by Bank Aceh Syariah is by deliberation, billing, rescheduling, re-requirement, rearrangement, and execution of collateral.